دور التمكين في نقل التمكين المعرفة بالدول العربية دراسة وصفية على مؤشرات مؤتمر المعرفة العربي لسنة 2016 ضمن برنامج الأمم المتحدة الإنمائي (Economic studies journal, 2019)
The study aims to define the concept of the strategy of empowering the workers and its requirements and its dimensions, as well as the role of the strategy of e Arab countries. The empowerment in the transfer and settlement of knowledge in ththe strategy of in problem of the study is to answer the main question: Is there a roletrain. empowerment inThe study found several results, the most important of which are: - The institutional framework on which the dimensions of technical education and vocational training are based suffers from slackness and weakness in the transfer and resettlement of knowledge, as well as the developmental efforts of some Arab countries in terms of higher education. This sector is linked to the creation of knowledge and development, as well as the weakness of most Arab countries in their spending on scientific research and development and the lack of preparation of researchers. The most important recommendations The Arab countries should reconsider their experiences and policies in -the study: Inrelation to the transfer and resettlement of various The aim is to create a national system to create a relationship between training and the labor market, and to control the concepts related to education, technical and vocational training, as well as to the building of a sound approach that will facilitate linking the higher emphasizeeducation sector by creating knowledge through providing the necessary means for this. Instead of increasing efforts and providing the necessary material and moral strengthening the human capacities necessary to upgrade the system of Andsupport research, development and innovation at various centers. -Technical education and vocational training .
Keywords: Empowerment strategy; Competitive economy; unicationComm Technology, Information -Higher education Research